Characteristics of Dyeing Cotton Thread Using Fine Particle Powder from Tectona Grandis Leaf - Dian W. Kurniawidi; Diah L. Dewi; Susi Rahayu; Arif Budianto; Siti Alaa (Postgraduate, University of Mataram, 2023)
In Lombok, the traditional process of dyeing woven fabrics primarily involves the use of synthetic dyes, which can contribute to environmental pollution. This study aimed to identify the characteristics of woven yarn and assess the effect of dye solution pH on yarn properties when using teak leaves (Tectona grandis) to produce dye powder through a mechanical thermal method. The thread coloring process comprised mordanting, coloring, and fixation stages, with the assistance of Android applications for color analysis and a Universal Tensile Machine Type RTG-1310 to assess mechanical properties. The results revealed that dyeing yarn with anthocyanin powder from teak leaves yielded a range of colors, including shades of gray, brown, and red. The highest tensile strength observed was 2,664 cN/dtex, and the solution's pH significantly influenced the dominant color, with red being prominent. Notably, optimal tensile strength (1,649 cN/dtex) was achieved at pH six. These findings highlight the potential for producing high-quality cotton threads using different dyeing processes and techniques. The study's insights contribute to both environmental protection and thread quality enhancement in the textile industry